Differences in Cardiovascular Risk, Coronary Artery Disease, and Cardiac Events Between Black and White Individuals Enrolled in the PROMISE Trial - Zhang, Lili; Olalere, Devvora; Mayrhofer, Thomas; Bittner, Daniel O.; Emami, Hamed; Meyersohn, Nina M.; Puchner, Stefan B.; Abidov, Aiden; Moloo, Jamaluddin; Dolor, Rowena J.; Mark, Daniel B.; Ferencik, Maros; et al. (JAMA Cardiology, 2021)
IMPORTANCE Race and ethnicity have been studied as risk factors in cardiovascular disease. How risk factors, epicardial coronary artery disease, and cardiac events differ between Black and White individuals undergoing noninvasive testing for coronary artery disease is not known.
CRIS-Team WoS Importer:2022-01-07